PENGARUH MANAJEMEN KELUARGA, GENERASI, DAN STRUKTUR KEPEMILIKAN TERHADAP KINERJA PERUSAHAAN KELUARGA YANG TERDAFTAR DI BURSA EFEK INDONESIA - Santi Yopie; Angellyn Lim (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2021)
The family company is an important and influential entity, especially in the economic sector. This study examines how family management, generations, ownership structure influence the performance of family companies listed on the Indonesia Stock Exchange (BEI). Ownership structure variables consist of family ownership, institutional ownership, foreign ownership and managerial ownership. Performance is measured by Tobin's Q and Return of Assets (ROA). This study examined 112 from all 135 family companies from 2016-2020. This research used e-views version 10 to test the data. The results of this study are family generation and foreign ownership have a significant positive effect, family management has a significant negative effect, while family ownership, institutional ownership, and managerial ownership have no significant effect on Tobin's Q. Then, institutional ownership has a significant positive effect, family generation has a negative effect, and family management, family ownership, foreigners, and managerial have no significant effect on ROA.